2013
DOI: 10.1186/1471-2164-14-333
|View full text |Cite
|
Sign up to set email alerts
|

Genomic and physiological variability within Group II (non-proteolytic) Clostridium botulinum

Abstract: BackgroundClostridium botulinum is a group of four physiologically and phylogenetically distinct bacteria that produce botulinum neurotoxin. While studies have characterised variability between strains of Group I (proteolytic) C. botulinum, the genetic and physiological variability and relationships between strains within Group II (non-proteolytic) C. botulinum are not well understood. In this study the genome of Group II strain C. botulinum Eklund 17B (NRP) was sequenced and used to construct a whole genome D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

8
68
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(76 citation statements)
references
References 31 publications
8
68
0
Order By: Relevance
“…2). These data confirm and extend reports by several groups which showed that genetic and/or genomic diversity of C. botulinum group II strains formed two distinct subpopulations (11,22,23).…”
Section: Resultssupporting
confidence: 81%
See 2 more Smart Citations
“…2). These data confirm and extend reports by several groups which showed that genetic and/or genomic diversity of C. botulinum group II strains formed two distinct subpopulations (11,22,23).…”
Section: Resultssupporting
confidence: 81%
“…However, three isolates (BE0211E1, BE0211E2, and BE0211E3) from a food sample (beluga) collected during a 2002 foodborne botulism outbreak in Kuujjuaq (outbreak 30) originally tested positive for BoNT/E using the mouse bioassay (Table 1 and data not shown). It is possible that these isolates have lost their neurotoxin genes, as reported for other group II C. botulinum strains (22,36).…”
Section: Resultsmentioning
confidence: 82%
See 1 more Smart Citation
“…C. botulinum E strain was isolated from a home-cured ham, and it was speculated that the contamination could have occurred from the seasoning, possibly sea salt, since other products (sausage and bacon) from the same pig were not contaminated (30). Since strain 84-10 shows a different subtype and MLST profile from strains isolated from fish and marine animals (8,13,31), it could represent a particular C. botulinum variant adapted to a specific environment or a specific host, such as pigs.…”
mentioning
confidence: 99%
“…enomic epidemiology has provided novel insights into the genetic characteristics and phylogenetic diversity of botulinum neurotoxin (BoNT)-producing Clostridium species (1)(2)(3)(4)(5)(6)(7)(8).…”
mentioning
confidence: 99%